An exploratory study on shopper typologies in Malaysia. - Wong, Yue-Teng; Osman, Syuhaily; Chan, Benjamin Yin-Fah (Canadian Academy of Oriental and Occidental Culture, 2011)
There is an increasing trend of Malaysians shopping for leisure and spending their free time in shopping malls. Consumer shopping behavior has a plethora of research done. However, little intention has been given to summarizing the salient conclusions that can be drawn from the extensive study of segmentation research on Asian populations, particularly in Malaysia. This study aims to profile different types of shopper typology based on psychographic market segmentation statements and its differences with shopping motives. The difference of gender in each cluster was examined. Quota sampling was used in selecting 200 respondents in one of the university in Malaysia. In brief, all the respondents can be grouped into three main groups namely, economic shoppers, addictive shoppers and convenience shoppers. There was difference in gender found among economic shoppers. Different types of shoppers might lead to different implications to retailing industry and specifically the management of shopping malls.Key words: Shopper Typology; Gender Differences; Shopping MotivesRésumé: Les malaisiens ont une tendance croissante de considérer le shopping comme un loisir et de passer plus de temps libre dans les centres commerciaux. Il y a une pléthore de recherches effectuées sur le comportement d'achat des consommateurs. Toutefois, on n’a guère prêté d’attention à résumer les conclusions les plus marquantes qui peuvent être tirées de l'étude approfondie de la recherche de segmentation sur les populations asiatiques, et en particulier en Malaisie. Cette étude vise à établir les différents types de la typologie de consommateurs sur la base des déclarations psychographiques de segmentation du marché et les différences avec des motifs commerciaux. La différence de sexe a été examinée dans chaque groupe. L'échantillonnage par quotas a été utilisée dans la sélection des 200 répondants dans l'une des universités en Malaisie. En bref, tous les répondants peuvent être regroupées en trois groupes principaux, à savoir les consommateurs économiques, les consommateurs accros et les consommateurs pour la commodité. Une différence de sexe a été constatée chez les acheteurs économiques. Différents types de consommateurs pourraient conduire à des conséquences différentes pour l'industrie de vente au détail et en particulier pour la gestion des centres commerciaux. Mots clés: Typologie de consommateur; Differences de sexe; Motifs commerciaux.